APPLICATION OF TEMPORARY FOOD STORAGE STANDARDS IN THE SECTION KITCHEN FOX HOTEL PEKANBARU - Neneng Setiawati; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the application of temporary food storage standards (parstock) in the section of kitchen Fox Hotel Pekanbaru. Food ingredients are  divided into two namely Perishable and groceries materials, storage of both materials must be applied continuously starting from the type of room and stroge equipment, temperature in terms of storage hygiene, food labeling, the method used and packaging until the material is ready to be processed in order to get good quality ingredients. This research uses research methods qualitative and to get the data author uses interview techniques, observation and documentation. From the results of research conducted by the author for 4 months at Fox Hotel Peanbaru, the results show that the storage is in good condition but does not meet the correct storage standards. Keywords : Storage Standards, Groceries, Perishable